Insect resistance management : biology, economics, and prediction - Onstad, David W. (Academic Press, 2014)
This book not only covers molecular to economic issues, but also transgenic crops, seed treatments and other pest management tactics such as crop rotation. It includes the importance of using Insect Resistance Management (IRM) in the integrated pest management paradigm, the need to study and account for pest behavior, and the influence of human behavior and decision making in IRM.